1999
DOI: 10.1046/j.1365-2044.1999.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of combined rectus sheath and ilioinguinal blocks for abdominal gynaecological surgery

Abstract: SummaryThe vasoactive properties of EMLA (eutectic mixture of local anaesthetic) and amethocaine were compared using Doppler colour ultrasound to measure vein diameter in 20 male volunteers. EMLA or amethocaine cream were applied over veins on the dorsum of the hand and vein diameter was measured prior to application of the preparations and at 1, 1.5 and 2 h after removal. Visual analogue scores for skin colour and vasodilatation were performed at 1 h. The results showed no significant difference in vein diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…A case report by Muir and Ferguson presented the successful use of single rectus sheath blocks, placed by a blind landmark technique, as a sole anesthetic for an umbilical hernia repair in an obese patient not suitable for central neuraxial anesthesia and deemed too high risk for general anesthesia [16]. Yentis described decreased opioid requirements following the use of blind injections bilaterally around the rectus sheath for midline incisions as well as rectus sheath blocks combined with ilioinguinal blocks for transverse incisions for gynecological surgery [17]. Cornish and Deacon described the surgical placement of rectus sheath catheters for analgesia in upper abdominal surgery as a technique that completely controlled the somatic component of pain and was beneficial in minimizing the use of opioids used for control of the visceral component of pain [18].…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Muir and Ferguson presented the successful use of single rectus sheath blocks, placed by a blind landmark technique, as a sole anesthetic for an umbilical hernia repair in an obese patient not suitable for central neuraxial anesthesia and deemed too high risk for general anesthesia [16]. Yentis described decreased opioid requirements following the use of blind injections bilaterally around the rectus sheath for midline incisions as well as rectus sheath blocks combined with ilioinguinal blocks for transverse incisions for gynecological surgery [17]. Cornish and Deacon described the surgical placement of rectus sheath catheters for analgesia in upper abdominal surgery as a technique that completely controlled the somatic component of pain and was beneficial in minimizing the use of opioids used for control of the visceral component of pain [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yentis et al [5] in 1999 compared in abdominal gynecological surgery combined supra-and infraumbilical bilateral rectus sheath block plus bilateral ilioinguinal block for midline incision vs. infraumbilical bilateral rectus sheath block plus bilateral ilioinguinal block plus bilateral deep subcutaneous LA infi ltration above the inguinal ligament for transverse incision using the scratch method. Th e authors found this additional combination of ilioinguinal block and deep subcutaneous LA infi ltration was required to block the skin and subcutaneous tissue of the lateral parts of the transverse incision.…”
Section: Resultsmentioning
confidence: 99%
“…The rectus sheath block in combination with ilio-inguinal nerve blocks has been described for abdominal gynaecological procedures in adults [11]. Hussein et al [12] reported to routinely perform combined bilateral ilio-inguinal and rectus sheath blocks for elective gynaecological operations involving a Pfannensteil incision.…”
Section: Discussionmentioning
confidence: 99%